2015
DOI: 10.1123/jcsp.2014-0052
|View full text |Cite
|
Sign up to set email alerts
|

Coach Pressure and Disordered Eating in Female Collegiate Athletes: Is the Coach-Athlete Relationship a Mediating Factor?

Abstract: When athletes “uncritically accept” the coaching expectations associated with their sport, negative health consequences (e.g., disordered eating behaviors, clinical eating disorders) may result. The coach’s influence on disordered eating behaviors may be a product of factors related to overconformity to the sport ethic, issues with coach communication regarding recommendations for weight management, and the strength of the coach-athlete relationship. The present study investigated perceived weight-related coac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…As reported by Muscat and Long (2008), negative comments from coaches and teammates can trigger body image disturbances or restrictive eating behaviors. In our series, perceived pressures from coaches were significantly associated with the presence of ED symptoms in female athletes competing in esthetic sports, supporting previous findings (e.g., Coker-Cranney and Reel, 2015). Our observation is also in accordance with Diaz et al (2019), who found that a considerable number of coaches showed weightrelated beliefs, attitudes, and practices that could potentially enhance the risk of EDs among the athletes under their care.…”
Section: Discussionsupporting
confidence: 91%
“…As reported by Muscat and Long (2008), negative comments from coaches and teammates can trigger body image disturbances or restrictive eating behaviors. In our series, perceived pressures from coaches were significantly associated with the presence of ED symptoms in female athletes competing in esthetic sports, supporting previous findings (e.g., Coker-Cranney and Reel, 2015). Our observation is also in accordance with Diaz et al (2019), who found that a considerable number of coaches showed weightrelated beliefs, attitudes, and practices that could potentially enhance the risk of EDs among the athletes under their care.…”
Section: Discussionsupporting
confidence: 91%
“…Athletes should be educated to recognise signs and behaviours that may be associated with eating disorders and RED-S, including overexercise, rigid eating patterns, amenorrhoea, a focus on thinness and a competitive comparison of physiques 299. A strong coach–athlete relationship may protect against eating disorders 300. Coaches need to understand the physiologic importance of proper nutrition and weight management 301–303.…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 99%
“…The sport environment has been shown to influence the risk of EDs, illness and premature death (Arcelus, Mitchell, Wales, & Nielsen, 2011) but may also play a vital role in minimizing ED risk and fostering recovery (Coker-Cranney & Reel, 2015). The aforementioned recommendations on the role of each MDTT member and considerations to support safe, appropriate treatment and training parameters, align with fostering an environment where the athlete is better able to navigate recovery and more consistently demonstrate an ability to adhere to treatment targets.…”
Section: Resultsmentioning
confidence: 99%